2015
DOI: 10.1007/8904_2015_458
|View full text |Cite
|
Sign up to set email alerts
|

Liver Fibrosis Associated with Iron Accumulation Due to Long-Term Heme-Arginate Treatment in Acute Intermittent Porphyria: A Case Series

Abstract: Acute intermittent porphyria (AIP) is an autoso-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 14 publications
1
42
1
Order By: Relevance
“… showed that during intravascular hemolysis leading to free haem excess, the liver is the most susceptible organ to haem overload, and when hemopexin capacity is exceeded, haem accumulates mainly in Küpffer cells. In line with our results, three well‐documented studies concerning recurrent AIP patients reported also that regular hemin infusions trigger variable liver iron overload .…”
Section: Discussionsupporting
confidence: 92%
“… showed that during intravascular hemolysis leading to free haem excess, the liver is the most susceptible organ to haem overload, and when hemopexin capacity is exceeded, haem accumulates mainly in Küpffer cells. In line with our results, three well‐documented studies concerning recurrent AIP patients reported also that regular hemin infusions trigger variable liver iron overload .…”
Section: Discussionsupporting
confidence: 92%
“…This risk is likely decreased when heme is administered as the heme‐albumin complex, which not only stabilizes the heme but also appears to diminish its toxicity to vascular endothelium. Other potential adverse effects of intravenous heme include transient thrombocytopenia and prolongation of prothrombin time (without resultant bleeding diathesis), hepatic iron overload (with repeated, chronic administration), and development of tachyphylaxis …”
Section: Management Of Acute Attacksmentioning
confidence: 99%
“…The standard cut-off scores of BDI-II are: minimal depression (0-9), mild depression (10)(11)(12)(13)(14)(15)(16)(17)(18); moderate depression (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) and severe depression . The standard cutoff scores of BAI are low anxiety (0-21), moderate anxiety (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) and severe anxiety (36-63).…”
Section: Discussionmentioning
confidence: 99%
“…Although heme represses ALAS, thus blocking heme biosynthesis, it also activates hemeoxygenase-1 (EC:1.14.99.3), which in turn promotes acute attack recurrences and the decline of the therapeutic efficacy (16,17). Thromboembolic disease and iron overload (a dose of 250 mg of heme arginate contains 22.7 mg of iron) are also side effects associated with repeated courses of this therapy (18). Even though prophylactic heme appears to be beneficial in patients with recurrent attacks, life-long exposure to drugs for the control of symptoms may cause considerable adverse events that greatly impair quality of life (16,17).…”
Section: Introductionmentioning
confidence: 98%